Identification and Evaluation of Lactic Acid Bacteria from Collagen Milk as Potential Probiotic Candidates - Suryani, Elsa Mega; Harmoko, Deni; Rosiah, Namrotur (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Collagen milk is a novel substrate that has rarely been investigated as a source of probiotic bacteria, despite its great potential as a functional food. This study aimed to isolate and characterize lactic acid bacteria (LAB) from collagen milk and to evaluate their tolerance to acidic conditions. The isolation and identification of LAB were conducted based on Gram staining, catalase testing, and cell morphology. Acid tolerance was assessed at pH 1, 2, and 3 to simulate gastric conditions. The results showed that a total of 21 LAB isolates were successfully obtained, most of which were rod-shaped and Gram-positive. Among these isolates, three superior strains SKF-174, SKF-106, and SKF-204 exhibited high tolerance to acidic environments, indicating their ability to survive under gastrointestinal conditions. These findings suggest that fermented collagen milk has the potential to serve as a promising source of probiotic lactic acid bacteria with strong acid resistance and desirable functional properties.